Toxic bait and mating disruption to control the American fruit fly and the oriental fruit moth on peach orchards - Härter, Wagner da Roza; Grützmacher, Anderson Dionei; Nava, Dori Edson; Gonçalves, Rafael da Silva; Botton, Marcos (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the simultaneous use of toxic bait and mating disruption technique using sexual pheromone for Anastrepha fraterculus and Grapholita molesta control, in commercial peach orchards. Three 0.5-ha orchards were used, with the following treatments: orchad 1, toxic bait (Biofruit 3% + Malathion 500 CE, 200 mL in 100 L) and mating disruption using sexual pheromone (Splat Grafo) in 1,000 points ha-1; orchad 2, conventional management, using contact insecticides 2 to 3 times a year; orchad 3, no pest control. Adult populations of both species, and sprout and fruit damages were monitored during the 2007/2008 and 2008/2009 crop seasons. Simultaneous use of toxic bait and mating disruption technique decreased the captures of A. fraterculus and G. molesta in more than 90%. In the two crop seasons, the damages on sprouts decreased 62–85%, and 98–99% on fruit, compared to the untreated orchard.